Middle and late Eocene fish otoliths from the eastern and southern USA - Lin, Chien-Hsiang; Nolf, Dirk (European Journal of Taxonomy, 2022)
The fossil otoliths of the southern USA have been known for more than 130 years and are among the richest assemblages worldwide. However, previous studies are often scattered and with outdated systematic scheme. A collection of over 25000 otoliths ranging in age from the Lutetian to the Priabonian from 47 sites in five states in the eastern and southern USA is analysed here. Combined with the earlier described material, at least 101 otolith-based taxa are documented, of which 83 are identified at species level. Fourteen of these are introduced as new species: Elopothrissus bernardlemorti sp. nov., “Muraenesox” barrytownensis sp. nov., Pseudophichthys texanus sp. nov., Paraconger wechesensis sp. nov., Neoopisthopterus weltoni sp. nov., “aff. Glyptophidium” stringeri sp. nov., Symmetrosulcus dockeryi sp. nov., Mene garviei sp. nov., “Citharus” varians sp. nov., Waitakia beelzebub sp. nov., Astroscopus compactus sp. nov., Parascombrops yanceyi sp. nov., Anisotremus rambo sp. nov., and Pagellus pamunkeyensis sp. nov. The assemblages are distinct fom contemporary European faunas by the complete lack of mesopelagic fish otoliths, and by the presence of sciaenids. Dominant taxa in the American Eocene are the Ophidiidae, Sciaenidae, Lactariidae, and Congridae. They indicate shallow-water environments for all the sampled sites. The notable abundance of those taxa suggests that they could have a higher turnover rate, and provided fundamental nutrition in the local Paleogene marine ecosystem. Further analyses of the species in the stratigraphic succession revealed that a faunal turnover between the Claiborne and Jackson seas was evident in teleosts, and it might be more widespread in other marine organisms in the region.